The GATS turns ten: A preliminary stocktaking - Rudolf Adlung (World Trade Organization (WTO), 2004)
The paper discusses the experience to date with the implementation and application of the General Agreement on Trade in Services (GATS), some ten years after its entry into force. One striking observation is the smooth functioning of the Agreement, which has created far less tensions and frictions, including at Ministerial Meetings, than its difficult negotiating history might have suggested. This is due in large part to a high degree of flexibility at several levels: Members have more scope than under the GATT to depart from common horizontal obligations, in particular the MFN principle; they are able to adjust the breadth and depth of their trade commitments (market access and national treatment) to particular sector conditions; and they face less constraints, if any, in the use of trade-related policies such as subsidies, export restrictions, or domestic regulatory interventions. An additional source of flexibility is the uncertainty still surrounding a few core concepts of the Agreement and their sometimes daring application in individual schedules. While the ongoing negotiations also provide an opportunity for technical corrections of scheduling problems, the basic (built-in) flexibility elements of the Agreement - including the bottom-up approach of undertaking sector commitments and the possibility of inscribing limitations under individual modes - will, of course, persist. (Their actual relevance may, nevertheless, differ significantly between 'old' Members and countries negotiating their accession to the WTO.) Given the broad reach of of the Agreement in terms of membership, sector application, and modal coverage, flexibility may be considered a conditio sine qua non. There is little reason to believe that a more rigid structure would have been acceptable to Uruguay Round participants and, even if so, that it would have proven stable and resilient over time. However, flexibility may come at a cost: lack of meaningful obligations across a reasonably broad range of service sectors. Vested interests may find it far easier than under the GATT to defend their privileges and defy more rational and harmonized trading conditions. While the paper discusses formula-based approaches that have been proposed to improve the quantity and/or quality of sector commitments within the existing framework of GATS, there should be no illusion about the scope for technical solutions to what constitutes a political and institutional challenge.
Keywords: F02; F13; H70; 330; WTO; Trade in Services; Rules; Liberalization; GATS